Central nervous system lymphoma: a description and analysis of patients’ clinical and radiological features (Medical Journal of Indonesia, 2014)
Background: Central nervous system (CNS) lymphoma is a rare brain neoplasm. Its incidence has increased these years, so it should be considered in the differential diagnosis for mass lesions in the CNS. The aim of the study was to describe the radiological and clinical features of patients with CNS lymphoma. Methods: The study was a retrospective study. All patients histopathologically confirmed to have CNS lymphoma from November 2008 to December 2013 in Siloam Hospital Lippo Village were included in the study. Medical records and patients’ MRI results were retrieved to be analyzed. Results: 32 patients were histopathologically diagnosed to have CNS lymphoma. The patients, mean age was 54 ± 15.01 years with slight male predominance. No patient was immuno compromised (CD4 > 500 cells/ÂµL and leukocyte 5,000-11,000 cells/µL). The median interval between the onset of the initial symptoms and diagnosis is 7 weeks. The most common presenting symptoms were headache, mental changes, and neurological deficits related to the location of lesion. MR images show that most lesions were enhanced with contrast, iso-hypointense in T1 weighted imaging (T1WI), iso- to hypointense with perifocal edema in T2 weighted imaging (T2WI), hyperintense in diffusion weighted imaging (DWI), with the most common location was white matter of cerebral hemisphere on one or more lobes and periventricular area, and the tumor could be single or multiple (24%) without clear edges. Conclusion: Short course of neurological worsening (within weeks) should lead a suspicion toward lymphoma. The characteristics of MR images are markedly enhanced by contrast, iso- to hypointense on T1WI and T2WI, and hyperintense in DWI, involving white matter of cerebral hemisphere and periventricular area.